Analisis Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran Al–Qur’an dan Hadits di Mts Ar-Ridho Medan - Muthi’ah; Robie Fanreza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As time progresses, technology continues to advance. The connection with learning about technological advancements is due to the fact that a good education system will produce excellent human resources and advance a country. The higher the quality of education in a country, the more advanced that country will become. Conversely, the poorer the quality of an education system in a country, the more it will lag behind. Teachers require new media to support learning. This need arises because the lecture method commonly used can seem monotonous. Therefore, students are less motivated to actively participate in learning. The purpose of this research is to increase the interest and motivation of students at MTs Ar-Ridho Medan in studying Islamic education subjects by utilizing and developing learning through Canva-based learning media. Teachers design this resource as a learning aid. This research is qualitative descriptive research. The results show that Canva-based learning media can be used by teachers, leading students to become interested in increasing their interest and motivation in learning at school. This research illustrates that the use of the Canva application in teaching the Quran and Hadith is engaging.